Resource allocation for real-time video coding system - Liu, Yang (2010)
A real-time communication requires a video coding strategy with high compression ratio to achieve the best video quality at a given bitrate, small buffer for low-delay interactive communication, low computing complexity for easy implementation with personal video application terminals (e.g. handphone and PDA), and high scalability to provide an embedded bitstream with adaptive capability for various video quality, frame rate and spatial resolution. This thesis investigates the existing video coding standards, especially the newest H. 264/AVC and its scalable extension. To produce the best visual quality of the reconstructed video with a given coding resource constraint and help meet the requirements of real-time communication, three aspects of resource allocation are considered in this thesis.